2021
DOI: 10.1186/s12913-021-06271-0
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of Cochlear implants in Swedish adults

Abstract: Background Research has shown unilateral cochlear implants (CIs) significantly improve clinical outcomes and quality of life in adults. However, only 13% of eligible Swedish adults currently use a unilateral CI. The objective was to estimate the cost-effectiveness of unilateral CIs compared to a hearing aid for Swedish adults with severe to profound hearing loss. Methods A Markov model with a lifetime horizon and six-month cycle length was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…With the inclusion of research groups with and without CI, the effects of CI on individuals with similar hearing impairment can be directly compared. Furthermore, it will be possible to see whether CI is as cost-effective in Belgian adults as it is in other high-income countries 63 64. By including patients with a unilateral hearing loss in this study, the impact of unilateral hearing loss on work performance and possible differences or similarities with bilaterally hearing-impaired patients can be explored.…”
Section: Discussionmentioning
confidence: 99%
“…With the inclusion of research groups with and without CI, the effects of CI on individuals with similar hearing impairment can be directly compared. Furthermore, it will be possible to see whether CI is as cost-effective in Belgian adults as it is in other high-income countries 63 64. By including patients with a unilateral hearing loss in this study, the impact of unilateral hearing loss on work performance and possible differences or similarities with bilaterally hearing-impaired patients can be explored.…”
Section: Discussionmentioning
confidence: 99%
“…(1) have an available post-operative flat panel volume computed tomography (fpVCT) image with a secondary reconstruction of 99 µm taken after their CI surgery (taken after the second implantation), (2) be at least 18 years old at the study start, (3) have postlingual bilateral deafness, (4) be a bilateral CI user with at least 6 months of experience with the SONNET 2 or RONDO 3 audio processor (MED-EL, Innsbruck, Austria), (5) have at least ten active electrode contacts on each side, (6) use the FSP, FS4, or FS4-p sound-coding strategy on each side, (7) have a speech understanding with the individual CI of ≥25% on a monosyllables test at 65 dB sound pressure level (SPL) or a speech reception threshold (SRT) of ≤20 dB signal-to-noise-ratio (SNR) on a sentence-in-noise test, (8) be willing and able to give feedback on the fitting map and process, and (9) give their signed and dated informed consent before participating in any study-related procedures. Candidates that did not fulfill the inclusion criteria were excluded.…”
Section: Participantsmentioning
confidence: 99%
“…In some countries, simultaneous bilateral CI provision in children younger than three years of age with bilateral sensorineural hearing loss is given funding priority over CI provision for other age groups and types of hearing loss [6]. In other countries, only unilateral implantation is funded in people with bilateral deafness [6][7][8]. A study on people who received bilateral CIs in their childhood demonstrated significant benefits of CI use, not only in the time frame where hearing and speech intelligibility develop, but also up to adulthood [9].…”
Section: Introductionmentioning
confidence: 99%
“…Health state utilities are numerical values representing an individual's preferences for different health-related states, where 0 corresponds to death and 1 corresponds to perfect health [23,24]. The utilities were multiplied by the time spent in a specific state to produce qualityadjusted life years (QALYs).…”
Section: Utilitiesmentioning
confidence: 99%